Sydney's Water-A Suitable Case for Private Treatment? - Chapman, Ross; Cuthbertson, Sandy (World Bank, Washington, DC, 2012)
Sydney Water, a statutory corporation responsible for capturing, storing, treating, and reticulating Sydney's water, has contracted for privately built, owned, and operated (BOO) treatment plants. By the end of the century, these plants will treat almost all the drinking water consumed in Sydney. The authors review the BOO bidding process, the risk-sharing arrangements between Sydney Water and the treatment companies, and the new regulatory process for setting water prices.